2008
DOI: 10.4049/jimmunol.180.4.2562
|View full text |Cite
|
Sign up to set email alerts
|

CCR2+ Monocyte-Derived Dendritic Cells and Exudate Macrophages Produce Influenza-Induced Pulmonary Immune Pathology and Mortality

Abstract: Infection with pathogenic influenza virus induces severe pulmonary immune pathology, but the specific cell types that cause this have not been determined. We characterized inflammatory cell types in mice that overexpress MCP-1 (CCL2) in the lungs, then examined those cells during influenza infection of wild-type (WT) mice. Lungs of both naive surfactant protein C-MCP mice and influenza-infected WT mice contain increased numbers of CCR2+ monocytes, monocyte-derived DC (moDC), and exudate macrophages (exMACs). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
495
3
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 405 publications
(544 citation statements)
references
References 55 publications
41
495
3
5
Order By: Relevance
“…45 Our gating strategy distinguishes ExMs from AMs, which are both CD11c ϩ AF ϩ on the basis of CD11b expression (present on ExMs and absent on AMs), as recently described. [33][34][35][36] In those studies, ExMs were specifically identified in the lungs of mice with bacterial or viral pneumonia, in which the numbers were much smaller than in the current study. The impressive quantity of ExMs that we identify in this model likely reflects the substantial inflammation induced by cryptococcal lung infection, with recruitment of up to 100 million CD45 ϩ leukocytes per mouse and critical reliance on lung macrophages for clearance of this organism.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…45 Our gating strategy distinguishes ExMs from AMs, which are both CD11c ϩ AF ϩ on the basis of CD11b expression (present on ExMs and absent on AMs), as recently described. [33][34][35][36] In those studies, ExMs were specifically identified in the lungs of mice with bacterial or viral pneumonia, in which the numbers were much smaller than in the current study. The impressive quantity of ExMs that we identify in this model likely reflects the substantial inflammation induced by cryptococcal lung infection, with recruitment of up to 100 million CD45 ϩ leukocytes per mouse and critical reliance on lung macrophages for clearance of this organism.…”
Section: Discussioncontrasting
confidence: 60%
“…Therefore, we evaluated ExM expression of the cell surface molecule Ly-6C as a marker of newly differentiated myeloid cells. 33,56,57 ExMs recovered at 7 dpi strongly express Ly-6C, whereas expression was diminished at 14 and 21 dpi (Figure 3). By 28 dpi, the few remaining ExMs expressed almost no Ly-6C.…”
Section: Exms Strongly Express Ly-6c During the Early Phase Of Their mentioning
confidence: 97%
See 2 more Smart Citations
“…2), and found that CD103 1 CD11b À DC migrate from their intraepithelial base to the draining MLN [2]. The disappearance of this CD11b À population from the trachea was accompanied by an influx of CD11b 1 DC, representing inflammatory-type Ly6C 1 DC [46]. Inflammatory DC expressed B220 and BST2 (120G8) in addition to high levels of CD11c and CD11b [14].…”
Section: Lung DC Subsets and Antiviral Immunity: Influenza As The Parmentioning
confidence: 99%